Impacto técnico e econômico da energia solar fotovoltaica em prédios públicos através de geração distribuída - Amaral, Ricardo Cézar do (2016)
Photovoltaic solar energy (PV) grows exponentially, since 2012 reaching levels of over 100 GWp installed worldwide. In this area the Brazilian industry just awakened through auctions, mainly aimed to Distributed Generation (DG). There are few large systems (1 MWp) of PV in an urban environment. Even though, since 2012, with the ANEEL's Normative Resolution 482 there was available law, these systems weren't economically feasible until 2014. This panorama, generates methodological opportunity to PV proposition to mapping potentials in public and city buildings; targeting creation of support policies, strategies and decision makers for solar energy investments in long terms and another consequences of management. It complements the stagnation gap at Brazilian Electric System (BES) as its business models of energy contracting from its captive environment, which has shown to be very innovative for PV at leading markets such as the USA. So, this study asks whether the Net Metering is sufficient, conducting comprehensive survey of Technical and Economic Feasibility for a case study to an utility company and an university (public sector) using PV at DG. The proposal sets 10% penetration targets in the utility and measuring its consequence impacts. It predicts 5 MWp as ideal project due to restrictions, 11.3 MWp to optimize the Net Metering system and 17 MWp to turn the University into a "Net Zero Building" (or zero costs electricity bill).